Games and Much More for the Modern Languages and Translation Class - Santamaría Urbieta, Alexandra; Alcalde Peñalver, Elena (Brill, 2025)
Dive into the future of language education with our guide, blending innovation with practical application. Unlock the power of gamification, digital storytelling, and AI to make learning more engaging and effective. Transform classes into dynamic, interactive experiences that captivate students. Master classroom response systems and utilize social networks to enhance educational outcomes. This book is a must-have for educators seeking to revolutionize their teaching methods and bring languages to life. Get ready to elevate your teaching strategies and inspire your students. Embrace the change and lead the way in modern language education.
Keywords: gamification; digital storytelling; translation class